KAWIN BEDA AGAMA: PERSPEKTIF PLURALISME-MULTIKULTURALISME - Syauqi Futaqi (Lembaga Studi Agama dan Masyarakat Aceh (LSAMA), 2017)
There are differences of opinion among scholars about the law of different religious marriage. There are opinions of scholars who forbid the absolute marriage of different religions. Instead there are groups of scholars allow different marriage. The last opinion takes a limited stance of allowing a different religious marriage only for Muslim men with the ahl al-Kitab woman. The difference of opinion of scholars about the different religious marriage actually revolves in the terminology ahl al-kitab, kafir and musyrik. Each group has an interpretive argument about both terms. It is therefore necessary to examine the two terms separately before determining their legal status.